Performance analysis of greenhouse dryer by using insulated north-wall under natural convection mode - Prashant Singh Chauhan; Anil Kumar (Energy Reports, 2016)
A prototype north wall insulated greenhouse dryer has been fabricated and tested in no-load conditions under natural convection mode. Experimentation has been conducted in two different cases. Case-I is when solar collector placed inside the dryer and Case-II is North wall insulated greenhouse dryer without solar collector. Coefficient of performance, heat utilisation factor, convective heat transfer coefficient and coefficient of diffusivity have been evaluated in thermal performance analysis. The difference of the highest convective heat transfer coefficient of both cases is 29.094W/m2êC which is showing the effectiveness of insulated north wall and solar collector. The maximum coefficient of diffusivity (0.0827) was achieved during the third day of experiment in Case-II. The inside room temperature of wall insulated greenhouse dryer for Case-I is 4.11%, 5.08 % and 11.61 % higher than the Case-II during the day 1, day 2 and day 3 respectively. This result is also showing the effectiveness of solar collector and insulated north wall. The highest heat utilisation factor (0.616) is obtained during the second day for Case-I while for Case-II it is 0.769 during the third day of experimentation. Maximum coefficient of performance achieved is 0.892 during the third day of the experiment for Case-I whereas 0.953 is obtained on the first day of experimentation for Case-II.
Keywords: 330; Coefficient of performance; Greenhouse dryer; Heat utilisation factor; Insulated north wall; Solar collector